Microsoft Windows Server AppFabric Cookbook : 60 Recipes for Getting the Most Out of WCF and WF Services, Including the Latest Capabilities in AppFabric 1.1 for Windows Server /: 60 Recipes for Getting the Most Out of WCF and WF Services, Including the Latest Capabilities in AppFabric 1.1 for Windows Server. (2012) - Unknown
No abstract available